2000
DOI: 10.1073/pnas.180317297
|View full text |Cite
|
Sign up to set email alerts
|

Cortical processing of change detection: Dissociation between natural vowels and two-frequency complex tones

Abstract: We compared magnetoencephalographic responses for natural vowels and for sounds consisting of two pure tones that represent the two lowest formant frequencies of these vowels. Our aim was to determine whether spectral changes in successive stimuli are detected differently for speech and nonspeech sounds. The stimuli were presented in four blocks applying an oddball paradigm (20% deviants, 80% standards): (i) /ɑ/ tokens as deviants vs. /i/ tokens as standards; (ii) /e/ vs. /i/; (iii) complex tones representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…This finding agrees with previous studies that have shown that, for speech sounds, the amplitude of the mismatch response depends on both native phoneme category membership and absolute acoustic difference from the standard (21). In common with Vihla et al (22), we found no significant difference in the mismatch response amplitude associated with the phoneme category deviants, D2 and D3, despite these being further away from each other in terms of acoustic difference than D2 is from the standard. Therefore, the main perceptual driver for mismatch response to D2 and D3 appears to be phoneme change rather than acoustic difference.…”
Section: Discussionsupporting
confidence: 90%
“…This finding agrees with previous studies that have shown that, for speech sounds, the amplitude of the mismatch response depends on both native phoneme category membership and absolute acoustic difference from the standard (21). In common with Vihla et al (22), we found no significant difference in the mismatch response amplitude associated with the phoneme category deviants, D2 and D3, despite these being further away from each other in terms of acoustic difference than D2 is from the standard. Therefore, the main perceptual driver for mismatch response to D2 and D3 appears to be phoneme change rather than acoustic difference.…”
Section: Discussionsupporting
confidence: 90%
“…An interesting twist to the way MMN parameters reflect differences between vowels and differences between complex tones consisting of the two lowest formant frequencies of those vowels was presented by Vihla et al [2000]. They found, as expected, that the complex tones produced larger MMN amplitude when the spectral differences were larger.…”
Section: Human Datamentioning
confidence: 67%
“…The special acoustic nature of speech is reflected in activation within the posterior superior temporal cortex [Benson et al, 2006;Vouloumanos et al, 2001] at around 100 ms [Eulitz et al, 1995;Tiitinen et al, 1999], especially in the left hemisphere [Parviainen et al, 2005]. Phonological categories seem to be available by 150-200 ms [Phillips et al, 2000;Vihla et al, 2000], after which the activation reflects higher-level linguistic processing [Connolly and Phillips, 1994;Helenius et al, 2002].…”
Section: Introductionmentioning
confidence: 99%